The relationship between economic hardship, self esteem and parental behavior among low-income mothers (Jurnal Kemanusiaan, 2017)
ABSTRACT This quantitative research attempts to examine the relationships between economic hardship, self-esteem, and parental behavior among low-income mothers. Specifically, the objectives of this research are to: 1) measure the relationship between economic hardship and self-esteem; 2) measure the relationship between economic hardship and parental behavior; 3) measure the relationship between self-esteem and parental behavior; and 4) measure the relationship between demographic aspects such as age and level of income with economic hardship, selfesteem and parental behavior. This research is based on a survey of 110 low-income mothers residing in Kota Kinabalu, Sabah. The instrument consisted of three dimensions: Economic Strain Questionnaire (ESQ) was used to measure economic hardship; Self-Esteem Inventories (SEI) to measure self-esteem; and Parent’s Report Scale (PR) to measure parental behavior. The validity and reliability of the entire three dimensions has been measured. The data was analyzed by descriptive and inferential statistics which involved mean, percentage, frequency, standard deviation and Pearson-correlation using the Statistical Packages for the Social Sciences (SPSS). The study showed that there was a negative relationship between economic hardship and self-esteem and a negative relationship between economic hardship and parental behavior. On the other hand, there was a positive relationship between self-esteem and parental behavior. The study also showed that there was a significant negative relationship between age and self-esteem, economic hardship, and parental behavior. Meanwhile, level of income was positively associated with self-esteem and parental behavior